Do Algorithms Dance? Viral Kids and Contagious Scripts: The infantile logic of spreadable media. (2nd January 2018) - Trezise, Bryoni
Abstract : In this article I discuss the genre of music video re-performance in the context of the formation and constitution of children's cultures and subjectivities. The viral dance-song cover, as I term it, is a digitally recorded and shared imitation of an iconic film or music video clip that formulates transmissible repertoires of movement and so becomes 'viral' in the process. Through examples taken from the Disney animation film Frozen and Sia's Chandelier, I think through the ways that contemporary childhood is not only visually construed, but energetically, affectively animated by the diffusive logic of the viral. In doing so I aim to understand how performances of the child-figure are transformed by the digital logic in which it operates, but also how the "traffic" of gesturality so exceedingly visualized by the logic of the viral cover signals a kind of performative compulsion towards transmissibility in which the behaviours of acting like a child become both tested and consolidated.